On the Biological Term “Gene” in the History of Science - Plischke, Kurt; Labisch, Alfons (ENDOXA, 2017)
Contemporary philosophy of science sets the origins of the predominant attributes of the term “gene” in the year 1900 when Gregor Mendel’s work was rediscovered. Yet it was the speculative biology of the second half of the 19th century that opened up the epistemic sphere for a new conception of heredity: heredity as the transmission of particulate, hereditable material units with a tendency for self-preservation. The then young discipline of biology dissociated its terminology from the preconceptions of natural philosophy. In the early 20th century, the postulated hereditary particles were associated with the chromosome and, at least in the 1940s, with nucleic acid: which was being stable and, at the same time, mutable, as well as capable of self-reproduction, self-selectivity, and memory. DNA epitomizes the perfect biological principle. But the most recent conception of the gene is not free from anthropomorphisms.